2013
DOI: 10.1260/0263-0923.32.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Roll Movement Control of a Spray Boom Structure Using Active Force Control with Artificial Neural Network Strategy

Abstract: Currently, most of modern sprayers are equipped with suspensions for improving the uniformity of spray application in the field. Therefore, this paper represents the possibility of applying active force control (AFC) technique for the control of a spray boom structure undesired roll movement through a simulation analysis. The dynamic model of the spray boom was firstly defined and an AFC-based scheme controller was designed and simulated in MATLAB environment.Artificial neural network (ANN) is incorporated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…The results reveal that the frequency-weighted root mean squared (RMS) accelerations of the controlled active seat suspension had a 34.1% decrease compared with that of a passive seat suspension. The suggested control algorithm was confirmed in the Another active force control system suggested by Tahmasebi et al [100] is the neuro active force control system. They believed this system was simple, effective and accurate.…”
Section: Appl Sci 2018 8 Xmentioning
confidence: 74%
See 1 more Smart Citation
“…The results reveal that the frequency-weighted root mean squared (RMS) accelerations of the controlled active seat suspension had a 34.1% decrease compared with that of a passive seat suspension. The suggested control algorithm was confirmed in the Another active force control system suggested by Tahmasebi et al [100] is the neuro active force control system. They believed this system was simple, effective and accurate.…”
Section: Appl Sci 2018 8 Xmentioning
confidence: 74%
“…Another active force control system suggested by Tahmasebi et al [100] is the neuro active force control system. They believed this system was simple, effective and accurate.…”
Section: Appl Sci 2018 8 Xmentioning
confidence: 99%
“…In addition, to ensure that the manipulator can perform in a greater workspace, the boom of a concrete pump truck structure should be more slender [6]. Robotic manipulators are also used in nuclear maintenance [7,8], for spraying large aircraft [9], etc. Under these circumstances, these robotic manipulators have to be designed as flexible-link manipulators (FLMs) with a slender structure.…”
Section: Introductionmentioning
confidence: 99%
“…When sprayer travels over undulating terrain, even small deformations of the structure can cause, by the large spray boom width, considerable displacements at the boom tips [3] . Lots of studies [4][5][6][7] has shown the unwanted movements of boom, rolling, yawing and jolting, are caused by spray vehicle roll as it travels over undulating terrain, dramatically affect the spray distribution pattern. Theoretical studies, simulations and field experiments have indicated that due to spray boom movements, spray deposit distribution varies between 0 and 800%.…”
Section: Introductionmentioning
confidence: 99%